Pengembangan Life Skill melalui Kegiatan Ekstrakurikuler Siswa MA NW Mengkuru Kecamatan Sakra Barat Lombok Timur - Lalu Sayuti; Abdul Fattah; Zainudin Zainudin (PALAPA, 2023)
Through education, it is hoped that students’ potential can be developed so that they have the courage to face life's problems without feeling pressured, have the will and ability, and are happy to develop themselves to be superior human beings. The objectives of this research were to describe the concepts, factors and development implications of life skill through students’ extracurricular activities at Mengkuru Nahdlatul Wathan Islamic Senior High School. This research was designed by using the qualitative method of informant finding in the field. The researcher used observation, interviews and documentation in data collection techniques. Describing the development concept of Life Skill was one of the analysis focuses in the development of education which emphasized the qualifications or skills to work. The study of life skill development through extracurricular activities of culinary art was discussed through students’ life study approach in the environment of Mengkuru Nahdlatul Wathan Islamic Senior High School starting from students’ lives, school activities, learning patterns, field practice, social activities among students and various other routines. The results of the research showed that Mengkuru Nahdlatul Wathan Islamic Senior High School tried to develop students' extracurricular activities with culinary art. In these activities, there were various kinds of menus which could provide satisfaction for students, teachers and the community, could increase students’ knowledge, and could be useful for many people.